Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Marie E. Spears Tiemann, December 27, 1988 - Tiemann, Marie E. Spearset al (1988)
Iowa Christmas bird counts of species found in Shenandoah contributed by Marie E. Spears Tiemann, December 27, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed